Back to the Future for Dermatophyte Genomics - Zeyana S. Rivera (American Society for Microbiology, 2012)
ABSTRACT Dermatophytes are a uniquely pathogenic group of fungi that cause most common fungal infections globally. The major cause of athlete’s foot is Trichophyton rubrum, a pathogen of human skin. A recent paper in this journal reported the sequencing and analysis of five additional genome sequences, including that of Trichophyton rubrum. These five join the existing two additional genome sequences to bring the total to seven dermatophyte genome sequences, a notable milestone in the study of these fungi. These additional genomes set the stage for future genome-supported studies on the biology, pathogenicity, and host specificity of this important group of pathogens. To predict how this future might play out, we review the history of Aspergillus genomics since the initial publication of the first three Aspergillus genome sequences in 2005, an event that stimulated important studies of the pathogenic Aspergillus species. From these 7 years of Aspergillus history, we offer some speculation on the future of dermatophyte studies supported by the genome sequences given the similarities, differences, and relative levels of support for studies in these two groups of fungi and the diseases they cause.